Antibacterial, Mechanical, and Thermal Properties of Ag, ZnO, TiO2 Reinforced PVA Nanocomposite Fibers - Duygulu, Nilüfer Evcimen; Altınbay, Aylin; Çiftçi, Fatih (Chemistry Europe, 2024)
This study investigated the effects of concentration and electrospinning parameters on the production of poly (vinyl alcohol) (PVA) nanofibers and examined the impact of reinforcing additives like nano-sized silver (Ag), titanium oxide (TiO2), and zinc oxide (ZnO) on these nanofibers. The PVA concentration was varied between 3 % and 10 % wt./v, while the flow rate was adjusted to 0.5, 1, and 5 ml/h. The optimal conditions for producing PVA nanofibers are a concentration of 10 % wt./v at a flow rate of 0.5 ml/h and an applied voltage of 9 kV, resulting in nanofibers with an average diameter of 502±0.10 nm. PVA nanofibers reinforced with nano-sized 3 % wt. Ag, TiO2, and ZnO and electrospun at optimum conditions. The morphological properties were determined using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM), and the average fiber diameter was measured with the Image J program. The presence of nanoparticles within the nanofibers was confirmed through Energy Dispersive Spectrometry (EDS) and X-ray diffraction (XRD). Chemical interactions of functional groups between PVA and ZnO, TiO2, and Ag NPs were analyzed with Fourier Transform Infrared Spectroscopy (FTIR), and thermal behaviors were studied with Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). Among the water absorption, Ag-reinforced PVA nanofibers showed maximum absorbance. Mechanical properties, evaluated through tensile testing, showed the elastic modulus of the nanocomposite fibers to be 38.07±12.01 MPa for PVA/Ag, 88.98±27.5 MPa for PVA/TiO2, and 30.56±9.77 MPa for PVA/ZnO. The antimicrobial activity of the nanoparticle-reinforced PVA nanofibers was tested using the agar disc diffusion method. The results showed that both Ag and TiO2 reinforced PVA nanocomposite fibers exhibited significant antimicrobial activity (gram–(Escherichia coli) and gram+(Staphylococcus aureus)), with inhibition zones of 8.48±0.08 cm against E. coli and 9.98±0.47 cm against S. aureus for Ag, and 4.32±0.02 cm against E. coli and 3.56±0.05 cm against S. aureus for TiO2.
Keywords: Electrospun; Nanoparticles; Composite Film; Antimicrobial